In the Making 8: Musical Networks and Algorithmic Emergence in the Times of Artificial Intelligence - Łukawski, Adam; In the Making 8: Musical Networks and Algorithmic Emergence in the Times of Artificial Intelligence West Den Haag, Den Haag, Netherlands 08/12/2024; Zeilinger, Martin (Rapenburg 70, 2311 EZ Leiden, Netherlands Academy of Creative and Performing Arts, Leiden University, 2024)
In the Making #8: Musical Networks and Algorithmic Emergence in the Times of Artificial IntelligenceThis public evening addresses the increasing entanglement of music, digital networks, and algorithmic processes in artistic practices today. As artificial intelligence and decentralized technologies gain prominence, they challenge traditional notions of creativity, authorship, and collaboration in the arts. Exploring these topics is crucial now, as they reshape not only how music is made and shared but also its aesthetic and social dimensions.Presenters: Adam Lukawski, with guests Martin Zeilinger and Sonia de Jager
FRIS
Editorial review
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music